Landscape of Anonymity: Transforming the Retired COVID-19 Field Medical Facility into A Memorial Park - Ma, Haotian; Chen, Siqing (Journal of Contemporary Urban Affairs, 2025)
During the COVID-19 emergency, the escalating number of cases overwhelmed the admission capacity of operating hospitals in many cities. The pandemic thus prompted the rapid construction of temporary field hospitals in cities like Wuhan, China, to relieve pressure on existing health infrastructure. While their operational phase has been well-documented, the post-pandemic reuse of these facilities remains underexplored. This study proposes a novel design paradigm - Anonymity Landscape Memorial Design - to transform the retired Huoshenshan Field Hospital into a public memorial park. Drawing on counter-memorial theory and spatial translation methods, the project reimagines commemorative landscapes through abstraction, emotional disruption, and interactive experience, rather than conventional symbolism. The design unfolds in four stages aligned with the emotional arc of the pandemic: outbreak, lockdown, recovery, and reflection. Methodologically, the study integrates multi-source data analysis, theoretical modeling, and adaptive reuse strategies to address spatial, social, and economic dimensions. Findings demonstrate how this approach fosters inclusive memory-making while yielding 62.5% material recycling and approximately CNY 7.94 million (US$1.10million) in cost savings. The project contributes a replicable framework for converting ephemeral urban infrastructure into resilient civic spaces that blend memory, sustainability, and public use. These outcomes demonstrate how post-pandemic urban transformations can reduce resource waste, strengthen local economies, enhance spatial equity, and expand access to quality civic spaces – offering insightful perspectives to other COVID-19-affected cities on similar issues of contemporary urbanisation.